Analysis of The Probability od Choosing a Public Transportation Mode Using A Binomial Model of Differential Logit - Farida farida; Agus Juanda; Shinta Novriani (Riviera Publishing, 2024)
Urbanization and mobility of the population have increased interest in efficient and convenient transportation systems, especially for trips from Cirebon to Jakarta via the Cipali toll road. Public transportation modes that can be used from Cirebon to Jakarta include buses, travel and trains. This study reviews public transportation buses and travel, focusing on the characteristics and probability of mode selection by travelers. The crucial factors studied are cost, travel time, and access time. Primary data was obtained from questionnaires using the stated preference method and secondary data obtained from related sources. The method used is linear regression modeling and binomial logit difference, which is obtained from data on travel cost (X1), travel time (X2), and travel access time (X3), which is tested using SPSS software with the regression equation obtained is Y = 2.386 + 0.251 X1.3 + X2 + 0.301 X1.4 + 0.497 X3.1. with a travel cost of Rp. 110,000 and with a travel time of 4 hours and 30 minutes, travelers prefer the bus mode (64.2%) with the most implicative attribute is the cost of travel, then the percentage value calculated using probability calculations and binomial models logits, the difference is (99.9%) choosing the bus and (0.1%) choosing travel. If the trevel wants to intensify the opportunity to choose the mode used by travelers with a percentage above 50%, then travel must reduce the fare at least Rp. 25,000 from the bus fare.